PENGARUH PEMBERIAN FILTRAT DAUN SAMBILOTO TERHADAP JUMLAH LEUKOSIT DARAH TIKUS PUTIH YANG TERPAPAR BENZENA - KHUMAIROH; Tjandrakirana, Tjandrakirana (Universitas Negeri Surabaya, 2013)
Benzene is a pollutant chemical environment and leukomogen factor. One?s of the effect is decrease leukocytes concentration because benzene can attack the enzyme topoisomerasse II in the bone marrow. The composition of Andrographis paniculata are deoxyndragrapholid, andrographolid, 14- deoxy-11, neoandrogapholid, 12- didehydroandrographolide, homoandrographolide, diterpenoid, and flavonoid, and the function is immunostimulan. This research aimed to prove that Andrographis paniculata leaf filtrate can increase leukocytes concentration caused inhalation exposure benzene. This subject are 25 Wistar strain male rats were divided into five groups; normal control (K0), benzene exposure control (K1), benzene exposure+Andrographis paniculata leaf filtrate 0,15 ml (P1), benzene exposure+Andrographis paniculata leaf filtrate 0,3 ml (P2) and benzene exposure+Andrographis paniculata leaf filtrate 0,45 ml (P3). Exposure benzene for 6 hours per day on 6 days and giving Andrographis paniculata leaf filtrate for 7 days. Counting leukocytes concentration uses a haemocytometer. Analysis of the data with One-Way ANOVA and LCD at 5 % level test. The result K1 decreased to 3063 cells/mm3 (thit(2.149)>ttab(2.02)), P1 increased to 6873 cells/mm3 (thit(2.709)>ttab(2.02)); P2 7627 cells/mm3 (thit(2.420)>ttab(2.02)); P3 8803 cells/mm3 (thit(2.124)>ttab(2.02)). The analysis revealed Andrographis paniculata leaf filtrate can increase leukocytes concentration (Fhit (648.18)>Ftab (2.87), LSD (222.23). The conclution of this research that Andrographis paniculata leaf filtrate can increase leukocytes level benzene exposure.